The laughing child: sex, interpretation, and laughter in Sigmund Freud's 'Analysis of a Phobia in a Five-Year-Old Boy' and Henry James's The Turn of the Screw. Issue 8 (14th September 2018) - Kindig, Patrick
ABSTRACT: This article reexamines moments of children's laughter in two texts key to the field of queer childhood studies, Freud's 'Analysis of a Phobia in a Five-Year-Old Boy' (1909) and Henry James's The Turn of the Screw (1898). Drawing on the Western philosophical tradition that theorises laughter as radical rupture, the article argues that the laugh of the child, insofar as it is capable of deflecting the analytical gaze of adults, poses a queer threat to adult projects of psychoanalytic interpretation. This leads the article to suggest that an attention to children's laughter might help us to queer the queer child a little further, allowing us to conceive of the relationship between children and sex in terms that are not always necessarily sexual.